Peningkatan pendapatan masyarakat Desa Parambambe Kabupaten Takalar melalui pemanfaatan lahan bekas galian batu bata - Sapto Haryoko; Hendra Jaya (DEDIKASI, 2020)
The purpose of the Community Partnership Program is to jointly develop a freshwater fishing business. Developing a fish breeding system with a cement pond system and a carpet pond system that will be adapted to the needs and conditions of the land. Provide training, direction, and marketing management regarding the cultivation of freshwater fish. Prevent damage to the surrounding environment due to excavation to be made into bricks. The methods of implementing Community Partnership Program (PKM) activities are lectures, simulations, discussions, and questions and answers through training in developing a freshwater fishery business, a fish maintenance system with a cement pond system and a carpet pond system, marketing management regarding the cultivation of freshwater fish, and counseling prevent environmental damage to the surrounding land due to excavation to be made of bricks to the community of South Galesong sub-district Takalar district. The trainees gained knowledge about the Utilization of Former Galian Bricks and their Impact on the environment, introduction of catfish farming techniques (Maintenance of seedlings to Sellability), introduction of catfish culture techniques (Marketing Management and Prospects), Manufacturing of Tarpaulin & Cement Ponds. Based on the results achieved, the implementation of training to residents (farmers) Parambambe Village, Galesong District, Takalar District can be successful because the percentage of training indicators can be achieved with a high score. So that at the end of the Camat training and the local government wishes to carry out the retraining of Takalar district.